The figure of the migrant in contemporary european cinema. - Corradi, Matias (Imagofagia, 2023)
Sobre Temenuga Trifonova. The figure of the migrant in contemporary european cinema. Nueva York: Bloomsbury Academic, 2020. 282 pp. ISBN 978-1-5013-6251-4.